The Controversies Surrounding Tocilizumab Administration Following Pathogen-Associated Molecular Pattern (PAMP) Induced by COVID-19 - Shayesteh Gheibi; Farhad Najmeddin; Bita Shahrami; Kourosh Sadeghi; Mojtaba Mojtahedzadeh (Research Center for Rational Use of Drugs (RCRUD), 2020)
A new corona virus disease (COVID-19) is affected more than 5 million people worldwide to date and has become a global pandemic. Since there is no definitive cure for this life threatening disease, many clinical studies are underway in this regard. Pathogen-associated molecular patterns (PAMP) prompting by coronavirus seems to generate cellular, structural, and functional derangement induced by immune dysregulation and many biological abnormalities including cytokine storm. The role of IL-6 in viral pneumonia and also the impact of its inhibition on the prevention of organ damage are not known yet.IL-6 seems to behave as a double blade evil cytokine, with a valuable role in cell to cell natural physiological communication. Tocilizumab as an inhibitor of interleukin (IL)-6, may interrupt the paracrine system while causing dissemination of bacterial, fungal, and other viral infections, especially COVID-19, who are at high-risk development of sepsis and life-threatening superinfection.